Efeito da cobertura do solo com palhiço de cana-de-açúcar na emergência de monocotiledôneas infestantes em campo - Silva Junior, Antonio Carlos da [UNESP] (2014)
With the implementation of mechanized harvesting of sugarcane, some features of its management have been modified since this system of crop leaves on the ground different quantities of straw, which can modify the management of weeds. The present study aimed to evaluate the effects of mulching with straw of sugarcane on the emergence of several weed species of the family Poaceae. The experiment was carrie out at the Experimental Farm of Lageado FCA / UNESP, on soil classified as Oxisol. Seven different amounts of soil mulches with straw sugarcane (0, 3, 6, 9, 12, 15 and 18 t ha-1) were evaluated. We used a variety SP83-2847 on seven species of weeds importance to culture, namely: Brachiaria decumbens, B. brizantha, B. ruziziensis, B. plantaginea, B. humidicola, Panicum maximum and Digitaria nuda . The experimental design was a randomized complete block with four replications. Each experimental unit contained seven species studied weeds and which were allocated in the central region of the plots, sowing at 1 cm depth in a set up area by species, which were later covered with a quantity of straw evenly distributed. Seeding rate was that there was emergency of 1,200 plant m-2. The study was two distinct steps. In the first step the emerged seedlings were evaluated in soil with coverage of straw and the second, seedlings emergence after removing the straw. Visible emerged seedlings were considered in each evaluation and more than 1 cm of shoots. The quantity of straw from cane sugar used as ground cover, influenced the dynamics of germination of different weed species studied. There was differential response of species as the amount of straw used. After removing the straw from sugarcane used as ground cover there was little germination in most species studied, with the exception of Digitaria nuda and Brachiaria plantaginea, while Panicum maximum was the species that showed smaller emergency ...